International Health Regulations (2005) facilitate communication for in-flight contacts of a Middle East respiratory syndrome case, Hong Kong Special Administrative Region, 2014 - Poon, Kwok-ming; Wong, Miu-ling; Leung, Yiu-hong; Sin, Ka-wai; To, May-kei Liza; Chuang, Shuk-kwan (Western Pacific Surveillance and Response, 2015)
A Hong Kong tour group has contacted a MERS case in a flight from Qatar to Austria. Communications under IHR (2005) have enabled efficient collaboration between health authorities across continents and our well-established preparedness plan of MERS has also ensured risk-based management in the emergency responses.